The Development of Legal Responsibility for a Socially Responsible Behavior for Business Operators in Romania, Member State of European Union - Laura Muresan (CES Working Papers, 2016)
Legal responsibility represents an important component of social responsibility, together with ethical responsibility, ecological responsibility, economical responsibility and philanthropic responsibility. The integration of social responsibility into the activity of business operators in the Member states of European Union is pursued at European Union level. The article analyses the opinion of the Brasov city citizens, in the framework of a marketing research performed in 2015, as regards the possibility that legal instruments should influence a socially responsible behavior for public or private business operators. The aspects analysed for business operators in Romania can represent a model for other European Union states as well.
Keywords: M31; L32; 330; social responsibility; public institutions; economic operators; quantitative marketing research; legal responsibility